Analisis Implementasi Peranan Produk Gadai Ar Rahn pada PT Pegadaian Kanwil 1 Medan - Alfaqih Tariq Azizy Hsb; Muhammad Yafiz (Universitas Muhammadiyah Enrekang, 2022)
The sharia pawnshop is a non-bank financial institution that provides financing transactions and pawn services based on Islamic sharia principles. The purpose of this study was to determine the quality of the role of pawn products in PT. Pawnshop Kanwil 1 Medan. This study uses qualitative methods with data collection techniques using literature studies and interviews from several customers at PT. Pawnshop Kanwil 1 Medan. The results of this study indicate the role of Rahn products plays a very important role in helping people get capital quickly and also customers are also free from the practice of usury.